Social gerontology a multidisciplinary perspective - Hooyman, Nancy R.; Kiyak, H. Asuman 1951- (Allyn & Bacon, 2011)
This textbook provides a survey of the field of social gerontology, taking a multi-disciplinary approach to the social aspects of aging and/or working with older adults. The authors demonstrate how age-related changes in the biological, functional, and psychological domains can influence the older person's interactions with his/her social and physical environment. They offer a view that presents aging positively, portraying concepts of active aging and resiliency, and defining "productive aging" by elaborating on the numerous ways elders contribute to society and their families. Based on the latest research findings, it offers understanding to critical issues of aging, attending to differences by age and cohort, gender, ethnic minority status, sexual orientation, and socio-economic status.